EDUCATIONAL VALUES IN THE FILM ENTITLED “GREEN BOOK” DIRECTED BY PETER FARRELLY - Sherlina Yuliyanti; Ch. Evy Tri Widyahening (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze the form of educational and moral values in the film entitled “Green Book”. The researcher used qualitative descriptive method. Watching the film, read the script, and taking note all data from film was the data collected by the researcher. The researcher used the validity triangulation data and triangulation theory to check validation. The result of the research showed that educational value in the Green Book film was character education and moral value in the Green Book film divided into 2 categories there were value of being and value of giving. Key Words: Educational Value, Moral Value, Character Education, Green Book Film.